Fatigue assessment of welded joints by means of the Strain Energy Density method: Numerical predictions and comparison with Eurocode 3: Numerical predictions and comparison with Eurocode 3 (Fracture and Structural Integrity, 2018)
The main aim of the present work is to investigate the effects of different parameters on the fatigue strength of four different welded details through an energetic approach based on the Strain Energy Density failurecriteria.The results of the finite element analyses have been compared with the fatigue strength predicted by the design guidance EN 1993-1-9:2005, also known as Eurocode 3, which establishes the rules for the fatigue design of steel welded joints.The results obtained in this work highlight an overestimation of the fatigue strength by the Eurocode 3 with regard to the details considered.
Keywords: Welding; Strain Energy Density method; Fatigue assessment; Finite element Analysis; Eurocode 3